Polymers Tailored for Controlled (Bio)degradation Through End-Group and In-Chain Functionalization - Rydz, Joanna; Musiol, Marta; Kowalczuk, Marek (Current Organic Synthesis, 2017)
Background: Currently, polymers can be created with specific properties that are tailored to a wide range of applications from medical to everyday products as packaging. There are different techniques to prepare novel polymer materials with various architectures and specific groups via a variety of reaction mechanisms of different complexity. End-group modification of polymers is a powerful tool for tailoring polymer properties. Objective: The review provides a brief description of the functional moieties and an outline of synthetic strategies used for tailoring the (bio)degradable polymer properties by end-group and in-chain functionalization. Conclusion: The contemporary synthetic strategies used in tailoring the (bio)degradable polymer properties by the end-group and in-chain functionalization demonstrate the importance of the relation between their subtle molecular structure, properties and function. When the development of (bio)degradable polymers is in its infancy the most crucial features are concentrated on the effect of macromolecular architecture, new monomer systems, polymerization mechanisms and different polymerization techniques on final (bio)degradable properties. Significant efforts have been directed towards the type of functional moieties and their influence on the degradation manner. Presented methods should help to design novel biodegradable polymeric materials and to avoid failures of the commercial products manufactured from them.
Keywords: controlled/living polymerization techniques